Pengaruh Budaya Kaizen Terhadap Kinerja Pegawai Kecamatan Bungah Kabupaten Gresik Dengan Kompensasi Sebagai Variabel Moderasi - Sutedja, Nanang; Gunawan, Moch Rizal Adi; Santoso, Rahmat Agus (Jurnal Mahasiswa Manajemen, 2023)
Background - Government performance measurement systems, both central and regional, began to be regulated since the issuance of Presidential Instruction (Inpres) Number 7 of 1999. The Presidential Instruction signifies the implementation of the Government Agency Accountability System (SAKIP) to increase government accountability and performance in Indonesia. One of the cultures implemented by the organization is the kaizen culture. Objective - This study aims to examine the effect of Kaizen Culture on Employee Performance in Bungah District, Gresik Regency with Compensation as a Moderating Variable. Design/Methodology/Approach - This research is a quantitative research with data collection techniques using research instruments, data analysis is statistical to test hypotheses. Findings - The results of this study indicate that Kaizen culture has a significant positive effect on employee performance. Compensation is not a moderating variable that moderates the relationship between Kaizen Culture and Employee Performance. Research implications - This research contributes to ASN employees to improve work skills and strengthen shared commitment in public service in order to achieve the target of community satisfaction. Research limitations - This research was only conducted on ASN employees in the Bungah District Office, Gresik Regency.